Hubungan Kemampuan Berfikir Kreatif dan Kecerdasan Emosional terhadap Kemandirian Belajar Biologi Peserta Didik Kelas XI MIPA SMAN 4 Bantaeng - Syahriani Yusuf; Yusminah Hala; Muhiddin Palennari (UNM Journal of Biological Education, 2023)
This study aims to find out about the extent to which students' creative thinking abilities, students' emotional intelligence, learning independence of class XI MIPA students at SMA Negeri 4 Bantaeng. As well as looking for whether there is a relationship and influence between the ability to think creatively with the independence of learning Biology students, the relationship between emotional intelligence and the independence of learning Biology students, the relationship between the ability to think creatively and emotional intelligence together with the independent learning of class XI MIPA SMA Negeri 4 Bantaeng in Bantaeng Regency South Sulawesi. This type of research is a quantitative research with ex post-facto type. The population in the study were all students of class XI MIPA at SMAN Negeri 4 Bantaeng in the 2021-2022 academic year, a total of 129 students. The research sample is 100 students using random sampling technique or random sampling. Data collection techniques are by questionnaire and essay test. Data were analyzed using descriptive and inferential statistical techniques. The results showed that (i) students' creative thinking skills were classified as moderate, (ii) students' emotional intelligence was classified as moderate (iii) students' science learning independence was in the moderate category, (iv) there was a relationship between creative thinking ability and student learning independence in class XI MIPA SMA Negeri 4 Bantaeng. (v) there is a relationship between emotional intelligence and learning independence of class XI MIPA students of SMA Negeri 4 Bantaeng. (vi) there is a relationship between creative thinking and emotional intelligence on the learning independence of class XI MIPA students of SMA Negeri 4 Bantaeng.